Analgesic Effect of Incisional Morphine Following Inguinal Herniotomy Under Spinal Anesthesia. Issue 2 (March 1996) - Rosenstock, C.; Andersen, G.; Antonsen, K.; Rasmussen, H.; Lund, C.
Abstract : Background and Objectives: Opioids have been shown to possess antinociceptive effects after peripheral administration in experimental and clinical studies. The results of clinical studies on intra-articularly administered morphine are, however, conflicting. The objective of this study was to examine a possible analgesic effect of incisionally administered morphine on postoperative pain in patients undergoing inguinal herniotomy. Methods: Forty outpatients were included in a double-blind, randomized, placebo-controlled study. The patients had spinal anesthesia with 1.5-2.0 mL hyperbaric 5% lidocaine. At conclusion of herniotomy morphine 5 mg was injected incisionally in 10 patients, intravenously in 10, and subcutaneously in 10. The placebo group of 10 patients had saline injected in the incision. Postoperative pain was assessed with a visual analog scale at rest and during mobilization. Assessments were made immediately before and at 0, 2, 4, and 6 hours after herniotomy and on the second and seventh postoperative days. At the same times morphine and acetaminophen consumptions were recorded. Results: There were no significant differences in postoperative visual analog scores between the groups. Except for the cumulative morphine requirement from the second to the seventh postoperative day, which was significantly higher in the placebo group than in other groups, no significant differences in cumulative morphine and acetaminophen requirements were found between the groups. Conclusions: A single 5-mg dose of morphine injected in the herniotomy wound did not affect pain scores or supplementary analgesic requirements, which argues against a role of peripheral opioid receptors in mediating analgesia.